The role of social support in antiretroviral therapy uptake and retention among pregnant and postpartum women living with HIV in the Greater Accra region of Ghana - Edward Kwabena Ameyaw; Jerry John Nutor; Jaffer Okiring; Isaac Yeboah; Pascal Agbadi; Monica Getahun; Wisdom Agbadi; Rachel G.A. Thompson (BMC, 2024)
Abstract Introduction The role of social support in antiretroviral therapy (ART) uptake and retention among pregnant and postpartum women in Ghana's capital, Accra, has received limited attention in the literature. This cross-sectional study extends existing knowledge by investigating the role of social support in ART adherence and retention among pregnant and postpartum women in Accra. Methods We implemented a cross-sectional study in eleven (11) public health facilities. Convenience sampling approach was used to recruit 180 participants, out of which 176 with completed data were included in the study. ART adherence in the three months preceding the survey (termed consistent uptake), and ART retention were the outcomes of interest. Initial analysis included descriptive statistics characterized by frequencies and percentages to describe the study population. In model building, we included all variables that had p-values of 0.2 or lesser in the bivariate analysis to minimize negative confounding. Overall, a two-sided p-value of < 0.05 was considered statistically significant. Data were analyzed using Stata version 14.1 (College Station, TX). Results In the multivariate model, we realized a lower odds trend between social support score and consistent ART adherence, however, this was insignificant. Similarly, both the univariate and multivariate models showed that social support has no relationship with ART retention. Meanwhile, urban residents had a higher prevalence of ART adherence (adjusted Prevalence ratio (aPR) = 2.04, CI = 1.12-3.73) relative to rural/peri-urban residents. As compared to those below age 30, women aged 30-34 (aPR = 0.58, CI = 0.34-0.98) and above 35 (aPR = 0.48, CI = 0.31-0.72) had lower prevalence of ART adherence Women who knew their partner's HIV status had lower prevalence of ART adherence compared to those who did not know (aPR = 0.62, CI = 0.43-0.91). Also, having a rival or co-wife was significantly associated with ART retention such that higher prevalence of ART adherence among women with rivals relative to those without rivals (aOR = 1.98, CI = 1.16-3.36). Conclusion Our study showed that social support does not play any essential role in ART adherence among the surveyed pregnant and postpartum women. Meanwhile, factors such as having a rival and being under the age of thirty play an instrumental role. The study has signaled the need for ART retention scale-up interventions to have a multi-pronged approach in order to identify the multitude of underlying factors, beyond social support, that enhance/impede efforts to achieve higher uptake and retention rates.